Defining a Standard Set of Patient-Reported Outcomes for Patients With Advanced Ovarian Cancer - Escudero-Vilaplana, Vicente; Bernal, Elsa; Casado, Gema; Collado-Borrell, Roberto; Diez-Fernández, Raúl; Fernández Román, Ana Beatriz; Folguera, Carlos; González-Cortijo, Lucía; Herrero-Fernández, Marta; Marquina, Gloria; Martínez Nieto, Concepción; Rodríguez, Miguel Angel; et al. (Frontiers in Oncology, 2022)
Purpose Advanced ovarian cancer (AOC) and its treatment cause several symptoms and impact on patients’ health-related quality of life (HRQoL). We aim to reach a consensus on the most relevant patient-reported outcome (PROs), the corresponding measures (PROMs), and measurement frequency during AOC patients’ follow-up from patients’ and healthcare professionals’ (HCP) perspective. Methods The project comprised: 1) literature review, 2) focus group with five patients, 3) nominal group with 16 HCP, 4) two round-Delphi consultations with patients and HCP, 5) final meeting with HCP. Delphi questionnaire assessed the relevance of each PRO and the appropriateness (A) and feasibility (F) of the PROM (1=strongly agree; 9=strongly disagree). The consensus was reached when ≥75% panelists rated it as ‘relevant’, ‘appropriate’, ‘feasible’ (score 7-9). Results A total of 56 HCP [51.8% Hospital Pharmacy; 41.1% Oncology; 3.6% Nursing; and 3.6% Psycho-oncology; mean time in specialty 12.5 (8.0) years] and 10 AOC patients [mean time diagnosis 5.4 (3.0) years] participated in the 1st round. All PROs achieved consensus regarding their relevance, except dry skin (58.0%). Agreement was reached for PRO-CTCAE to be used to assess fatigue (A:84.9%; F:75.8%), neuropathy (A:92.4%; F:77.3%), diarrhea (A:87.9%; F:88.7%), constipation (A:86.4%; F:75.8%), nausea (A:89.4%; F:75.8%), insomnia (A:81.8%; F:88.7%), abdominal bloating (A:82.2%; F:82.2%) and sexuality (A:78.8%; F:88.6%); EQ-5D to determine patients’ HRQoL (A:87.9%; F:80.3%), pain (A:87.9%; F:75.8%) and mood (A:77.7%; F:85.5%); to assess treatment adherence the Morisky-Green (A:90.9%; F:84.9%) and the dispensing register (A:80.3%; F:80.3%) were chosen. It was agreed to note in the medical record whether the patient's treatment preferences had been considered during decision-making (A:78.8%; F:78.8%) and to use a 5-point Likert scale to assess treatment satisfaction (A:86.4%; F:86.4%). Panelists agreed (A:92.4%; F: 77.3%) to collect these PROs (1) at the time of diagnosis/relapse; (2) one month after starting treatment/change therapeutic strategy; (3) every three months during the 1st-year of treatment; and later (4) every six months until treatment completion/change. Conclusions The consensus reached represents the first step towards including the patient's perspective in AOC follow-up. The standardized collection of PROs in clinical practice may contribute to optimizing the follow-up of these patients and thus improving the quality of care..